IMMU-18. IMMUNOGENOMIC RESPONDER PHENOTYPE FROM A PHASE I TRIAL OF ANTI-LAG3 OR ANTI-CD137 ALONE AND IN COMBINATION WITH ANTI-PD-1 IN PATIENTS WITH RECURRENT GBM. (11th November 2019) - Jackson, Christina; Choi, John; Zhang, JiaJia; Piotrowski, Anna; Walbert, Tobias; Desai, Arati; Ahluwalia, Manmeet; Nabors, Burt; Ye, Xiaobu; Desideri, Serena; Fisher, Joy; Wen, Patrick; et al.
Abstract: BACKGROUND: Immune checkpoint inhibitors (ICIs) are not uniformly effective in glioblastoma treatment. Immunogenomic determinants may identify patients who are most likely to benefit from these therapies. Therefore, we compared the immunogenomic phenotype of a responder to combination anti-LAG-3 and anti-PD-1 therapy to non-responders. METHODS: We performed T cell receptor (TCR) sequencing and gene expression analysis on pre-treatment, post-chemoradiation, and post-immunotherapy tumor specimens of glioblastoma patients treated with anti-LAG3 in combination with anti-PD-1 after first recurrence (NCT02658981, ongoing). We evaluated T cell clonotypes and immunophenotype of serially collected peripheral blood mononuclear cells (PBMCs) during treatment using multi-parametric flow cytometry. RESULTS: To date, six patients have been enrolled in the initial anti-LAG-3 and anti-PD-1 cohort. One patient demonstrated complete response, one had stable disease, and four had progressive disease by radiographic evaluation. The responder demonstrated substantially higher TCR clonality in the resected tumor at initial diagnosis compared to non-responders (mean 0.028 vs. 0.005). Shared tumor infiltrating clonotypes with pre-immunotherapy PBMCs exhibited an increase in frequency from initial resection (6.8%) to resection at recurrence (20%). The responder's tumor at initial resection exhibited increased gene signatures of PD1 low CD8+ T cells, chemokine signaling, and interferon gamma pathways. On PBMC phenotypic analysis, the responder demonstrated significantly higher percentages of CD137+ CD8+T cells (median 8.38% vs 3.24%, p=0.02) and lower percentages of Foxp3+CD137+ CD4+T cells compared to non-responders (median 18.5% vs. 38.5%, p=0.006). Interestingly, dynamic analysis of PBMCs showed that the responder demonstrated a lower percentage of PD1+ CD8+ T cells pre-immunotherapy (median 2.5% vs.12.4%, p=0.002), with persistent decrease over the course of treatment while non-responders showed no consistent pattern. CONCLUSION: Our preliminary results demonstrate significant differences in tumor and peripheral blood immunogenomic characteristics between responder and non-responders to anti-LAG3 and anti-PD-1 therapy. These immunogenomic characteristics may help stratify patients' response to combination ICIs.